Does Financial Integration Spur Economic Growth? New Evidence from the First Era of Financial Globalization - Moritz Schularick; Thomas M. Steger (ETH Zurich, CER-ETH - Center of Economic Research, 2006)
Does international financial integration boost economic growth? The question has been discussed controversially for a long time, and a large number of studies has been devoted to its empirical investigation. As of yet, robust evidence for a positive impact of capital market integration on economic growth is lacking, as documented by Edison et al. (2002). However, there is substantial narrative evidence from economic history that highlights the contribution European capital made to economic growth of peripheral economies during the so-called first age of financial globalization before 1914. For this paper, we have compiled the first comprehensive data set to test econometrically if capital market integration had a positive impact on economic growth before WW1. Using the same models and techniques as contemporary studies, we show that there was indeed a significant and robust growth effect of international financial integration in the first era of financial globalization. Our temptative explanation for this marked difference between now and then stresses property rights protection as a prerequisite for the standard neoclassical model to work properly.
Keywords: F15; F21; F30; N10; N20; O11; O16; 330; International financial integration; Economic growth; First era of globalization; Globalisierung; Internationaler Finanzmarkt; Marktintegration; Wirtschaftswachstum; Wirtschaftsgeschichte